Investigating the Association Between Economic Conditions and Sports Performance in Asia: A Panel Data Approach - Mochammad Fahlevi; Kittisak Jermsittiparsert; Watcharin Joemsittiprasert; Oytun Sözüdoğru; Talip Emiroğlu; Mohammed Aljuaid (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
Knowing the factors that influence a nation's sporting performance can aid in formulating appropriate policies and plans. This study examines the relationship between gross domestic product, population, total debt, inflation, and trade as a proportion of GDP for eleven Asian nations from 1998 to 2018. Panel unit root tests, cointegration tests, and finally, Fully Modified Ordinary Least Square (FMLOS) were used to examine the relationships between the variables. The panel results revealed that GDP and TRD favorably and significantly impact national sports performance, whereas POP and TD have a negative impact. INF was discovered to have a negligible effect on national athletic performance. Hence, we suggest that Asian nations take appropriate measures to boost national sporting achievements.